Limitations on mobility due to COVID-19 and opinion on democracy - Huesca González, Ana María; Conde Belmonte, José Enrique (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article aims to highlight the restrictions imposed by the Spanish State on freedom of movement. Once these restrictions are described in the first three waves of the Covid-19 pandemic, we reflect on the possible excesses of the government by increasing its control over a concerned citizenry and in fear of the pandemic. However, there is an unexpected consequence in people’s political attitudes: a reduction in preferences towards democracy, in favor of authoritarianism.